A control algorithm to increase the efficient operation of wind energy conversion systems under extreme wind conditions - Nyam Jargalsaikhan (17380429) (2022)
This paper aims to increase the power production of gearless permanent magnet synchronous generator (PMSG) based wind energy conversion systems (WECS) in strong (greater than 25 m/s) wind speed regions. In general, most wind turbines cut off when wind speed is over the cut-out rate; as a result, the power generation of the wind farm decreases. This study introduces the look-up table pitch angle and rotational speed control to generate extra power in a strong wind region. Consequently, WECS can produce electric power at a reduced level until the wind speed reaches 35 m/s and the possibility of shutting down the wind turbines decreases. The proposed algorithm decreases the mechanical stress of wind turbine by decelerating rotational speed rather than turbine torque in strong wind regions. Furthermore, the model predictive control (MPC) is proposed to replace the PI controller in the inner current loop of the rotor speed control loop, thereby improving the performance of the stator current track. The proposed control method is validated in Matlab/SimPowerSystem software. The simulation result confirms that the proposed control method reduces the possibility of shutdown and guarantees temporally power production in strong wind conditions. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2022.08.243